FOPID controller design for pneumatic control valves with ultra-low overshoot, rapid response and enhanced robustness - Yuxin He; Aixiang Ma; Yuehui Wang; Xinyi Tian; Sihai Zhao (Scientific Reports)
Abstract The performance of pneumatic control valves, characterized by speed, stability, and accuracy, is critical for industrial production and energy efficiency. Traditional PID and fuzzy control methods face limitations in achieving high-precision control due to structural constraints. This study proposes a fractional-order proportional-integral-derivative (FOPID) controller optimized for pneumatic control valves, incorporating a novel overshoot-penalty objective function. To enhance optimization, the Hippopotamus Optimization (HO) is improved with Genetic Algorithm (GA). Simulation and experimental results demonstrate the proposed GAHO-based FOPID controller achieves a settling time of 5.25 s and an overshoot of 0.88%, significantly surpassing conventional methods. These results establish that the proposed FOPID controller as an effective solution for improving the stability, efficiency, and safety of pneumatic control systems in industrial applications.